Ion Implantation and Activation - Volume 3. - Suzuki, Kunihiro (Ion Implantation and Activation., 2013)
Ion Implantation and Activation presents the derivation process of related models in a comprehensive step by step manner starting from the fundamental processes and moving up into the more advanced theories. Chapters in the book explain, in depth, various topics such as Pearson functions, LSS theory, Monte Carlo simulations, Edgeworth Polynomials and much more. This book provides advanced engineering and physics students and researchers with complete and coherent coverage of modern semiconductor process modeling.